Newly founded Italian Cities of the Thirties. Ideologies, Theories and Technical achievements (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
Abstract: Although the new cities are to be considered a course against the current in modern culture in the twentieth century, they delineate an original significance that, in fact, belongs to the contemporary, because it deals with an unresolved problem: the methodological continuity between town planning and architecture. The new cities founded in Italy in the thirties, and in particular those of the Agro Pontino, make this antithesis emerge, and therefore they have often returned, in these last decades, to the center of the debate. And this not only for a historical research that studied an experimental sample not yet well investigated, but above all for a question related to the way of building the city. Here, this is precisely the problem: how do you build a city? In Italy there are, in those years, many ways of responding to this question. However, two are the most obvious poles. On one side are the planners, on the other, the architects. In between there is a keyword launched from Mussolini, taken by Giuseppe Bottai, taken over by many urban planners and many architects: â€˜disurbanamentoâ€™. Town planners are trying to find an autonomous discipline that moves town design (edilizia cittadina) â€“ close to Gustavo Giovannoniâ€™s ideas â€“ from an intuitive discipline to a real scientific subject, with procedures, methods, especially with a scalar of intervention, proportionate to the different geographical entities.Â